2021
DOI: 10.1159/000516888
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Core Burden Index Assessed by Near-Infrared Spectroscopy of Symptomatic Carotid Plaques: Association with Magnetic Resonance T1-Weighted Imaging

Abstract: <b><i>Introduction:</i></b> Vulnerable plaques are a strong predictor of cerebrovascular ischemic events, and high lipid core plaques (LCPs) are associated with an increased risk of embolic infarcts during carotid artery stenting (CAS). Recent developments in magnetic resonance (MR) plaque imaging have enabled noninvasive assessment of carotid plaque vulnerability, and the lipid component and intraplaque hemorrhage (IPH) are visible as high signal intensity areas on T1-weighted MR image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The present study focused on the degree of lipid component of carotid plaque detected by NIRS in patients undergoing CAS compared with the efficacy of avoiding cerebral embolisms between dual-layered and first-generation stents. Our results appear consistent with these previous findings 17 32. In high-LCP lesions, the ipsilateral embolism rate was significantly lower with dual-layered stents than with first-generation stents.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study focused on the degree of lipid component of carotid plaque detected by NIRS in patients undergoing CAS compared with the efficacy of avoiding cerebral embolisms between dual-layered and first-generation stents. Our results appear consistent with these previous findings 17 32. In high-LCP lesions, the ipsilateral embolism rate was significantly lower with dual-layered stents than with first-generation stents.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, no symptomatic plaque protrusion occurred in the dual-layered stent group, although asymptomatic plaque protrusion occurred in four cases, probably due to the inner shaft-pushing maneuver during deployment of the dual-layered stent in early-phase cases. A recent study suggested that high LCP as assessed by NIRS correlates with the SIR of MRI in patients with unstable plaques and a significant linear correlation was present between max-LCBI MLA and TIW-SIR MLA (r=−0.610, p<0.0001) 17. The present study focused on the degree of lipid component of carotid plaque detected by NIRS in patients undergoing CAS compared with the efficacy of avoiding cerebral embolisms between dual-layered and first-generation stents.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation